GAMBARAN RHEUMATOID ARTHRITIS (RA) PADA LANSIA DI KELURAHAN ANTANG - Rosdiana mus; Sutia Waidoba; Hairuddin Kudding; Mutmainnah Abbas; Dylan Tamalsir (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran, 2023)
Rheumatoid Arthritis (RA) is a progresive autoimune disease and chronic inflammation that attacks the musculoskeletal system but can include organs and body system as a whole, and synovial tissue damage occurs along with impaired mobility accompanied by premature death. RA is a chronic autoimmune inflammatory disorder or autoimmune response. A person’s immune system can be compromised and lowered, which destroys the joints andd lining of the synovial organs, especially the hands, feet, and kness. This study aims to find an overview of RA in the elderly on Kelurahan Antang. The research method used is observational criteria,elderly aged 56-65 years, have symptoms of join pain. The inspection method used is the latex slide ttest method.The results obtanied from 15samples obtained negattive RF examination, with the age group 56-65 years consisting of 2 men and 13 women. Therefore, the conclusion from the 15 research samples was negative RF examination results from all respondents.